Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Rewrite in simplest terms: 3(-3f – 2) – f


Sagot :

Answer:

53f

Step-by-step explanation:

3(-3f -2) -f

first expand the expression

=(-3f*3) (-2*3)-f

=(-9f)*(-6)-f

=54f-(1)f

=53f

Tasyha

Answer:

[tex] - 10f - 6[/tex]

Step-by-step explanation:

[tex]3( - 3f - 2) - f[/tex]

[tex] - 3 \times 3f - 3 \times 2[/tex]

[tex] - 9f - 3 \times 2[/tex]

[tex] - 9f - 6 - f[/tex]

[tex] - 9f - f = - 9f - 1f[/tex]

[tex]( - 9 - 1) f = - 10f[/tex]

[tex]\boxed{\green{ = - 10f - 6}}[/tex]